The effectiveness of social protection in five African countries through normal times and times of crisis - Katrin Gasior; Iva V. Tasseva; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We study the effectiveness of social protection benefits in reducing income and consumption poverty in five sub-Saharan African countries-Ghana, Mozambique, Tanzania, Uganda, and Zambia-in normal times and times of widespread economic crisis. Using tax-benefit microsimulation models with representative household survey data, first we estimate the coverage of benefits and their poverty-reducing effects in each country. Second, we study the ability of benefit automatic stabilizers to reduce losses in incomes and consumption in times of crisis, by simulating hypothetical reductions to earnings and employment. Although the coverage of benefits is fairly high in Ghana and Zambia, the poverty-reducing impact of benefits in all five countries is low in normal times. The effectiveness of benefits to stabilize income and consumption in times of crisis is also limited because many benefits are linked to proxies of income, not income itself, or have tight eligibility criteria. Social assistance programmes are typically unresponsive to losses in household earnings and employment and provide limited support for unemployed people.
Keywords: D31; H55; I3; 330; income and consumption poverty; social protection benefits; benefit automatic stabilizers; crisis